'I wish my health professionals understood that it's not just all about your HbA1c!'. Qualitative responses from the second Diabetes MILES – Australia (MILES‐2) study. Issue 6 (5th February 2020) - Litterbach, E.; Holmes‐Truscott, E.; Pouwer, F.; Speight, J.; Hendrieckx, C.
Abstract: Aims: Optimal diabetes management requires daily selfmanagement. While little time is spent with health professionals, they can have a substantial impact on how a person manages and feels about living with diabetes. The aim of this qualitative study was to explore what people with diabetes wish their health professionals understood about living with diabetes. Methods: Thematic analysis was conducted of responses to a single open‐ended question, 'What do you wish your health professional understood about living with diabetes?', which was part of the Diabetes MILES‐2 survey, assessing the psychological and behavioural aspects of living with type 1 or type 2 diabetes in Australian adults. Results: In total, 1316 responses (56% response rate) were collected, with 1190 responses included for analysis (54% from respondents with type 1 diabetes, 46% from those with type 2 diabetes). Seven major themes emerged; respondents wished their health professional understood: 1) the potential barriers to diabetes management; 2) that it is 'easier said than done'; 3) the social/emotional impact; 4) that they want, need and deserve more; 5) that judgements, assumptions and negative perspective are not helpful; 6) more about diabetes; and 7) that the respondent is the expert in his/her diabetes. Other comments suggested satisfactory experiences with health professionals, highlighting that some respondents had no wish for their health professional to understand more. Conclusions: This study highlights that, although some adults with diabetes are satisfied with their health professionals' understanding of living with diabetes, many report unmet needs and perceive a lack of person‐centred care from their health professionals. What's new?: Satisfactory encounters and relationships with health professionals play a crucial role in a person's diabetes self‐management and outcomes. This large‐scale, qualitative study highlights that some adults living with diabetes are satisfied with their health professionals' understanding, while others wish their health professional understood more about the challenges of living with diabetes, such as the complexity and full impact of the condition, that judgements/assumptions are not helpful, and that they are experts in their own diabetes. Health professionals need to better implement current, evidence‐based policies and guidelines, which focus on providing empathic, non‐judgemental, patient‐centred care.